Dual-antigen fusion protein vaccination induces protective immunity against Candida albicans infection in mice - Keran Jia; Yanhao Zhang; Mengyu Jiang; Mengge Cui; Jia Wang; Jiajia Zhang; Hua Wang; Huihai Zhao; Mengyan Li; Quanming Zou; Hao Zeng (Human Vaccines & Immunotherapeutics)
Candida albicans Is a leading cause of nosocomial bloodstream infections, particularly in immunocompromised patients. Current therapeutic strategies are insufficient, highlighting the need for effective vaccines. This study aimed to evaluate the efficacy of a dual-antigen fusion protein vaccine (AH) targeting the Als3 and Hyr1 proteins of C. albicans, using AlPO4 as an adjuvant. The AH vaccine was constructed by fusing Als317-432 and Hyr125-350 proteins, and its immunogenicity was tested in BALB/c mice and New Zealand white rabbits. Mice received three intramuscular doses of the vaccine combined with AlPO4, followed by a lethal challenge with C. albicans SC5314. Survival rates, antibody responses, cytokine production, fungal burdens, and organ pathology were assessed. The vaccine’s efficacy was also validated using rabbit serum. Mice vaccinated with the AH-AlPO4 combination exhibited significantly higher antibody titers, particularly IgG and its subclasses, compared to controls (p < .001). The survival rate of vaccinated mice was 80% post-infection, significantly higher than the control group (p < .01). Vaccinated mice showed reduced fungal loads in the blood, kidneys, spleen, and liver (p < .05). Increased levels of interferon gamma and interleukin (IL)-17A were observed, indicating robust T helper (Th) 1 and Th17 cell responses. Vaccination mitigated organ damage, with kidney and liver pathology scores significantly lower than those of unvaccinated mice (p < .05). Rabbit serum with polyclonal antibodies demonstrated effective antifungal activity, confirming vaccine efficacy across species. The AH-AlPO4 vaccine effectively induced strong immune responses, reduced fungal burden, and protected against organ pathology in C. albicans infections. These findings support further development of dual-antigen vaccine strategies.